Analisis Penerapan Risiko Kredit Dan Risiko Operasional Terhadap Pertumbuhan Laba Perbankan - Komala, Cahya; Arifin, M (LPPM Institut Bisnis dan Informatika Kesatuan, 2018)
For users of financial statements and business people in economic decision making requires information about the condition and financial performance of the company. Risk analysis is an alternative to test whether banking risks are useful for predicting future earnings growth. Well, managed risks can provide benefits to banks in generating profits or revenues. Financial users and business users in assessing a banking company not only see the profit generated in one period but continuously monitor the profit growth from year to year. This study was conducted by using multiple linear regression analysis, in three banking companies, namely PT. Bank Negara Indonesia Persero Tbk., PT. Bank Rakyat Indonesia Persero Tbk. and PT. Bank Mandiri Persero Tbk. The data used are financial reports for 10 years, from 2008-2017. The results showed that (1) simultaneously Credit Risk (NPL) and Operational Risk (BOPO) have no significant effect on Banking Profit Growth, which obtained from significant value is 0,060; (2) partially Credit Risk (NPL) has a significant effect on Profit Growth, which obtained from significant value is equal to 0,021. The higher the NPL, the company's profit will decrease. While Operational Risk (BOPO) has an insignificant effect on Banking Profit Growth, which is obtained from the significant value is 0.735. The source of bank income does not only come from operating income, but non-operating income also plays a role in increasing the bank's income resulting in profit growth